PENERAPAN PENCATATAN KEUANGAN BAGI UMKM BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH (SAK – EMKM) PADA PERUSAHAAN JENANG TEGUH RAHARJO PONOROGO - Arilia, Diah Kristina; Munari, Munari (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
ABSTRACT This study describes: (1) the process financial statements preparation in Jenang Teguh Raharjo company, (2) the obstacles that occurred during the preparation of financial statements, (3) how the company comprehended the presentation of financial statements based on SAK – EMKM or the Standard of Financial Accoutning for Micro Scale and Medium Enterprises (MSME). This qualitative study was performed using a descriptive design. Data of this study were collected through observation, interviews, and document analysis. The results showed that; (1) Teguh Raharjo company did not implement the SAK – EMKM standard, (2) financial statement was prepared based on personal capability, (3) the company realized that the financial statement of the company could not accurately project the business development.